Legacy of culture heritage building revitalization: place attachment and culture identity - Chan, Suk Ha Grace; Lee, Wing Han Helen; Tang, Binglin Martin; Chen, Ziyi (Frontiers in Psychology, 2024)
Introduction Cultural heritage buildings are revitalized to promote culture instead of being neglected or demolished. For locals, the revitalization of heritage buildings symbolizes a commitment to the community and a taste of collective memory. The study attempts to test the effectiveness of heritage cultural building on visitors’ post-experience behavior through cultural identity and place attachment. “Cultural activities engagement” and “knowledge transfer” serves as moderating attributes. Their moderating the effects on cultural identity and place attachment are examined, respectively. Method A valid sample size of 348 from four heritage buildings located in Hong Kong: Tai Kwun, Police Married Quarters (PMQ), Mei Ho House and The Mills. A data analysis platform for PLSSEM is chosen for this study. Results Results demonstrate that the effectiveness of heritage building revitalization on visitors’ local cultural identity and emotions leading to place attachment. Discussion In our study, the effectiveness of heritage building encompasses three elements which includes appearance and components; technology and planning as well as contribution. Knowledge transfer positively moderates the effectiveness of heritage building revitalization and cultural identity. However, cultural activity engagement negatively moderates place attachment. Findings also exhibit that place attachment in heritage building revitalization leads to a positive experience extension. For the practical contribution, the study provides insights to policy makers and planners for historic building design such as appearance and components, technology in facilitating local visitors’ local identity.